Axial compressive strength of welded S460 steel columns at elevated temperatures. (August 2018) - Fang, Han; Chan, Tak-Ming
Abstract: This paper presents an investigation on the structural performance of welded S460 steel columns under axial compression at elevated temperatures using finite element analysis. Stub and long columns with box and H- sections were considered. A new stress-strain curve model for S460 steel at elevated temperatures was proposed and adopted to obtain the stress-strain curves for the finite element analysis. A finite element model was developed and verified against the available test data for welded S460 steel columns subject to axial compression at room and elevated temperatures. A parametric study was carried out to generate additional data of the axial compressive strength of box and H-section columns with various cross-section slenderness and column slenderness ratios at elevated temperatures. The obtained numerical results of the column strength were compared with the design predictions using the European and American specifications and the direct strength method by substituting the material properties at elevated temperatures. It was found that the provisions in European and American standards for elevated temperature conditions provide relatively conservative predictions. The direct strength method overestimates the strength of stub columns while accurately predicts the strength of long columns at elevated temperatures. Modifications are proposed for the European and American standards and direct strength method and these modified design rules are recommended to be used to more accurately estimate the design strength for welded S460 steel columns at elevated temperatures. Highlights: Strength of welded S460 steel columns at elevated temperatures was investigated. A stress-strain curve model was validated for S460 steel at elevated temperatures. The methodology of finite element analysis (FEA) was validated for the investigation. Strength predictions based on three design rules were compared with FEA results. Modifications to the three design rules were proposed for structural design.